2021
DOI: 10.2217/imt-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib, a JAK1/JAK2 Selective Inhibitor, Ameliorates Acute and Chronic Steroid-Refractory Gvhd Mouse Models

Abstract: Aim: Graft-versus-host disease (GvHD) is a major complication arising in patients undergoing allogenic hematopoietic stem cell transplantation. Material & methods: We tested ruxolitinib (a selective JAK1/2 inhibitor) efficacy in three different preclinical models of GvHD. Results: Ruxolitinib, at doses that mimic clinically achievable human JAK/signal transducers and activators of transcription target inhibition, significantly reduced alloreactive T-cell activation and infiltration in the lung and skin, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The JAK1/2 signaling plays an important role in the mechasims of GVHD through mediating the activation and proinflammatoy cytokines release of T cell, neutrophils and dendritic cells (DCs) ( 40 , 41 ). Preclinical studies suggested that ruxolitinib can effectively inhibit JAK1/2 signaling, and ameliorate both acute and chronic GVHD while preserving graft-versus-tumor activity ( 42 , 43 ). For patients with steroid-refractory aGVHD, ruxolitinib orally given at a dose of 5–10 mg achieved a ORR at day 28 of 55–82% with acceptable toxicity ( 24 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The JAK1/2 signaling plays an important role in the mechasims of GVHD through mediating the activation and proinflammatoy cytokines release of T cell, neutrophils and dendritic cells (DCs) ( 40 , 41 ). Preclinical studies suggested that ruxolitinib can effectively inhibit JAK1/2 signaling, and ameliorate both acute and chronic GVHD while preserving graft-versus-tumor activity ( 42 , 43 ). For patients with steroid-refractory aGVHD, ruxolitinib orally given at a dose of 5–10 mg achieved a ORR at day 28 of 55–82% with acceptable toxicity ( 24 , 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies on ruxolitinib among those with SCD. Studies are showing promising results for ruxolitinib among those undergoing HSCT that encounter steroid refractory graft-versus host disease [34]. Still, these findings are limited among those with SCD and often include younger populations.…”
Section: Scdmentioning
confidence: 99%
“…Ab, antibody; BTK, Bruton’s Tyrosine Kinase; CAR Treg, chimeric antigen receptor T regulatory cell; ECP, extracorporeal photopheresis; FoxP3, forkhead box P3; H-Y Ab, antibodies specific for male (Y) antigens; MCP-1, monocyte chemoattractant protein-1; iNKT, invariant NK T cells; ROCK2, Rho associated coiled-coil containing protein kinase 2; sBAFF, soluble B-cell activating factor; SYK, spleen sssociated tyrosine kinase; TNF-α, tumor necrosis factor alpha. Reference citations used: 5 , 7 , 20 , 21 , 22 , 25 , 27 , 33 , 39 , 43 , 45 , 48 , 53 , 55 , 57 , 58 , 63 , 64 , 72 , 74 , 75 , 96 , 99 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , …”
Section: Introductionmentioning
confidence: 99%